Dahsyatnya kesusasteraan memerihalkan kehidupan - Sohaimi Abdul Aziz ([Glugor], Pulau Pinang : Penerbit Universiti Sains Malaysia, 2014)
History and criticism of social aspects and Malay literature.
Includes bibliographical references (page 158) and index.
In Malay.
Keywords: Malay literature -- History and criticism; Malay literature -- Social aspects